Gambaran Pengetahuan Perawat tentang Mobilisasi Progresif di Ruangan Intensive Care Unit (ICU) - Kadri, Hasyim (3031-8572, 2023)
Total bed rest for a long time can make the patient experience a decline in medical conditions. Bed rest is a risk factor for infection, contractures, decubitus ulcers, and blood clots. Stating that after 2 weeks of bed rest, there can be a loss of muscle mass of 5% -9% and a decrease in muscle strength of up to 20% -27%. Bed rest patients experience many negative effects including neuromuscular dysfunction, thromboembolism, atelectasis, pressure sores, and decreased limb function. Ewens. The aim of this research is to find out the description of nurses' knowledge about progressive mobilization in the Intensive Care Unit (ICU), Nurdin Hamzah Muaro Sabak Hospital. This research is a quantitative study with a cross sectional design. The population in this study were 23 ICU nurses at Nurdin Hamzah Hospital, using a total sampling technique with a sample of 23 respondents. Data obtained using a questionnaire. The statistical test used is the Chi-square test. The results of the study were 23 respondents with the highest knowledge being 19 respondents (82.6%). So it can be concluded that the respondents in this study had more high knowledge than those with low knowledge.Â